Diagnosis of pulmonary hemorrhagic leptospirosis complicated by invasive pulmonary aspergillosis complemented by metagenomic next-generation sequencing: a case report - Yang, Qiong-Fang; Shu, Cai-Min; Ji, Qiao-Ying (Frontiers in Medicine, 2024)
Background: Leptospirosis is a bacterial zoonosis with variable clinical manifestations.Pulmonary diffuse hemorrhagic leptospirosis often occurs rapidly and, when not promptly diagnosed and treated, it can be life-threatening. Aspergillus flavus is an opportunistic fungus that is commonly seen in immunosuppressed patients. Invasive pulmonary aspergillosis also progresses rapidly. This case study describes a patient with severe pneumonia caused by pulmonary hemorrhagic leptospirosis combined with invasive pulmonary aspergillosis. We have found almost no clinical reports to date on these two diseases occurring in the same patient.Case presentation: A 73-year-old male arrived at our hospital complaining of fever, general malaise, and hemoptysis that had lasted 4 days. The patient was initially diagnosed with severe pneumonia in the emergency department, but he did not respond well to empiric antibiotics.Subsequently, the patient's condition worsened and was transferred to the ICU ward after emergency tracheal intubation and invasive ventilator. In the ICU, antibacterial drugs were adjusted to treat bacteria and fungi extensively. Although the inflammatory indices decreased, the patient still had recurrent fever, and a series of etiological tests were negative. Finally, metagenomic next-generation sequencing (mNGS) of bronchial alveolar lavage fluid detected Leptospira interrogans and Aspergillus flavus. After targeted treatment with penicillin G and voriconazole, the patient's condition improved rapidly, and he was eventually transferred out of the ICU and recovered.Early recognition and diagnosis of leptospirosis is difficult, especially when a patient is co-infected with other pathogens. The use of mNGS to detect pathogens in bronchial alveolar lavage fluid is conducive to early diagnosis and treatment of the disease, and may significantly improve the prognosis in severe cases.